Dynamic Macsherry Model with Heredity Included - Alimov Kh.T.; Parovik R.I (Genius Journals, 2023)
Mathematical modeling in biophysical systems is essential. For example, a study of the work of the heart based on the contraction of its muscles. This article proposes a new mathematical model for constructing an artificial electrocardiogram of a healthy person, and develops a numerical solution algorithm based on finite difference schemes.
Keywords: ECG morphology; Heart rate variability; Dynamic model